HR Analytics Responsiveness in the Times of Covid-19 - Bishnoi, Rekha; Arora, Poonam (Indian Journal of Computer Science, 2021)
HR Analytics in an era of pandemic is playing a vital role in aligning all the functions of HR processes towards business outcome and giving competitive advantage. Disruption in economy and business has impact on both employers and employees in various ways. This becomes important to gauge the impact of COVID-19 and relevance of HR Analytics in the present era. This paper attempts to find the relevance and responsiveness of HR Analytics in remote working. There are different challenges in front of organizations due to sudden outbreak of Coronavirus. This paper depicts how HR Analytics is playing a crucial role in tapping COVID infection among employees and managing employees at worksite and remotely implementing various HR analytics strategies.